Pengaruh Waktu Panen Terhadap Daya Simpan Benih Kacang Panjang (Vigna sinensis L.) - ANGGARA, I MADE BAGUS; RAKA, I GUSTI NGURAH; NYANA, I DEWA NYOMAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.8, No.3, Juli 2019, 2019)
Effect of Harvest Time on the Save of Long Bean Seeds (Vigna sinensis L.). Supervised   Long bean plants have indeterminate growth type, ie vegetative growth is still active even though it has entered the generative growth phase. The indeterminate growth type causes the pods to form cook not at the same time. When harvesting long bean pods for quality seed production, it needs to be studied. The seeds before planting must undergo a process of storing both short and long term storage, so the seeds saving power that produced from the time of harvesting different pods also needs to be studied. This study used a completely randomized design (CRD) with three treatments when harvesting pods for seeds, namely physiological pre-cooking, harvesting at physiological ripe, and harvest after physiological cooking. The treatment was repeated nine times. The results showed that the treatment of harvest time had an effect on the shelf life of the beans. Harvest time when physiologically cooked has the longest shelf life compared to harvest time after or before physiological cooking. Seed quality when harvested physiologically during storage obtained the highest compared with the quality of seed yields before and after physiological cooking.